2014
DOI: 10.5005/jp-journals-10008-1155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Calcium Channel Blockers on Intraocular Pressure in Steroid-induced Glaucoma

Abstract: Purpose: To evaluate the effect of 0.125% verapamil and 0.5% diltiazem eye drops on intraocular pressure (IOP) in steroid-induced glaucoma in rabbit eyes.Methods: A total of 18 rabbits with steroid-induced glaucoma were divided into three groups (A, B and C; n = 6 each). Right eyes in groups A, B and C received 0.5% diltiazem, 0.125% verapamil and 0.5% timolol eye drops twice daily for 12 days, respectively; whereas, left eyes received distilled water. IOP was measured with Tono-pen XL at baseline, day 4, day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Rabbit's experimental studies reported the hypotensive effect of a single topical administration dose of flunarizine after 1 h [33]. Our findings are consistent with Ashutosh et al [34] and Irina et al [35] reported a preventable effect of CCBs on glucose-and adrenaline-induced acute glaucoma in rabbits. In addition, the previous studies show that levamlodipine has a good impact on decreasing IOP in rabbits' chronic glaucoma models [15].…”
Section: Discussionsupporting
confidence: 91%
“…Rabbit's experimental studies reported the hypotensive effect of a single topical administration dose of flunarizine after 1 h [33]. Our findings are consistent with Ashutosh et al [34] and Irina et al [35] reported a preventable effect of CCBs on glucose-and adrenaline-induced acute glaucoma in rabbits. In addition, the previous studies show that levamlodipine has a good impact on decreasing IOP in rabbits' chronic glaucoma models [15].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated a link between Ca 2+ , calcium channels and glaucoma 44 – 53 , providing a historical backdrop for our discovery of the role of Cacna2d1 in IOP modulation. Because Ca 2+ likely plays a role in the pathophysiology of glaucoma 45 , systemic calcium channel blockers (CCBs) (e.g., verapamil, diltiazem, or nimodipine) have been evaluated as plausible therapies for POAG.…”
Section: Discussionmentioning
confidence: 98%
“…Because Ca 2+ likely plays a role in the pathophysiology of glaucoma 45 , systemic calcium channel blockers (CCBs) (e.g., verapamil, diltiazem, or nimodipine) have been evaluated as plausible therapies for POAG. However, the outcomes of these investigations have been inconsistent, with some studies demonstrating that CCBs are effective in lowering IOP, protecting ganglion cells, increasing ocular blood flow and improving visual function while others fail to replicate those results 46 53 . In all studies performed to date, however, CCBs have targeted the α1 pore of the Ca 2+ channel and have used a systemic route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…These may thereby produce disease-causing signals and contribute to severe pathologies as those observed in heart failure, muscular dystrophy, diabetes, or neurodegenerative diseases [10, 11]. Also, considering the potential role of calcium channel blockers in treatment of glaucoma [12], RYR2 may be a potential candidate in POAG.…”
Section: Introductionmentioning
confidence: 99%